PUBLIC PERCEPTION OF VIGILANTISM IN THE FIGHT AGAINST HIGHWAY CRIME IN MORO LOCAL GOVERNMENT AREA, KWARA STATE, NIGERIA (2022)
This paper examines public perception of the effectiveness of Moro Community Vigilante Group (MCVG) in the fight against crimes along major highways that run through Moro Local Government Area, Kwara State. This study employs the mixed method research design utilizing both the quantitative and qualitative research designs using questionnaire, in - depth interview and focus group discussion. The respondents were selected through a purposive sampling technique and the participant exclusion criterion was used to recruit and prepare the participants. Key individuals who are familiar with the topic were nominated. The study reveals that the MCVG is a useful tool for curbing highway crimes in Moro Local Government Area, Kwara State, Nigeria. However, the study also discovers some major challenges undermining the effectiveness of the MCVG in the prevention against highway crimes and other related crimes in the region. Thus, the study recommends that there is the need to strengthen the supervisory capacity of the Nigerian Police Force so that it can effectively monitor the activities of vigilante groups and proactively respond to distress calls from these irregular security outfits. There is also the need for government support in the areas of training and basic operational equipment. Above all, there is need for the urgent rehabilitation of the roads that run through the council areas connecting Ilorin, the state capital to Kwara North Senatorial District and the rest of Southwest Nigeria up to Northern Nigeria